On the practical μ-stability of solutions of standard systems with delay - Martynyuk, A. A.; Sun', Chzhen-tsi (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We study the problem of μ-stability of a dynamical system with delay. Conditions of the practical μ-stability are established for the general case and for a quasilinear system. The conditions suggested are illustrated by an example.